Penyuntingan Teks Cerita Rakyat Nusantara Berbasis Pendidikan Karakter untuk Media Pembelajaran Tingkat Sekolah Dasar - Sri Enggar Kencana Dewi; Suryani; Tri Ratna Dewi; Resti Septikasari; Ratih Purnama Pertiwi (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2022)
The purpose of this study was to edit the book Collection of Indonesian Folklore (KCRN) with a focus on editing the simplification of language and condensing the content of the story by referring to character education so that the folklore can be used as a medium of learning for the SD/MI level. The method used is the descriptive analysis method. This research has four main steps namely; 1. Read KCRN carefully, 2. Identify elements that are not in accordance with character education (SD/MI), 3. Determine folklore that will be further edited, and 4. Conduct character education-based editing. Based on the results of the study, there were 24 folk tales that did not meet the criteria and there were 12 filk tales that met the criteria and the character education-based children’s stories had been edited so that they could be used as learning media for SD/MI education level (lower level/class).